2013
DOI: 10.1161/circulationaha.112.128751
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Pressure in Pregnancy and Subsequent Chronic Disease Risk

Abstract: Background Preeclampsia, a new-onset hypertensive disorder of pregnancy, is associated with lifetime cardiovascular disease risk, but less is known about risk after other pregnancy-related hypertension. Methods and Results The Northern Finland Birth Cohort 1966 included all expected births from 1 year (N=12 055 women). Blood pressure measurements and other prospective data were determined from prenatal care records and questionnaires for 10 314 women. Subsequent diagnoses were ascertained from Finnish regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
224
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(236 citation statements)
references
References 41 publications
(66 reference statements)
6
224
1
5
Order By: Relevance
“…A study of a Finnish cohort with 39 years of follow‐up found that GH was associated with modestly higher CVD risk than preeclampsia (HR: 1.45 versus 1.40) 44. Of note, the risk of future coronary artery disease, heart failure, hypertension, cerebrovascular disease, DM, and chronic kidney disease in this study were all found to be higher with GH than with preeclampsia in this study.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdsupporting
confidence: 40%
See 2 more Smart Citations
“…A study of a Finnish cohort with 39 years of follow‐up found that GH was associated with modestly higher CVD risk than preeclampsia (HR: 1.45 versus 1.40) 44. Of note, the risk of future coronary artery disease, heart failure, hypertension, cerebrovascular disease, DM, and chronic kidney disease in this study were all found to be higher with GH than with preeclampsia in this study.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdsupporting
confidence: 40%
“…More specifically, one meta‐analysis demonstrated a 4.2‐fold increased risk of heart failure, a 2.5‐fold increased risk of coronary artery disease, and a 1.8‐fold increased risk of stroke in women with preeclamptic pregnancies over a follow‐up period of up to 39 years 42. The risk of future hypertension is even more pronounced, with increased risk ranging from 2.3‐ to 6.7‐fold among women with prior preeclampsia 38, 40, 43, 44. These women also have roughly double the risk of venous thromboembolism and 4 times the risk of DM compared with those with normotensive pregnancies 38, 45.…”
Section: Hdp and Long‐term Risk Of Maternal Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing prevalence of overweight and obesity worldwide,20 aside from increasing AF prevalence, may also partially account for the increase in HPD prevalence 8, 21. The increase in AF in women with a history of HPD may be as a direct consequence of persistent structural and functional myocardial changes that occur during HPDs; or future hypertension that occurs earlier in life6 and at higher rates in women with HPD versus those with normotensive pregnancies 5. An echocardiographic study evaluating the prevalence of left ventricular hypertrophy following hypertensive pregnancy showed that the increase in prevalence was likely explained by a longer duration of chronic hypertension 13.…”
Section: Discussionmentioning
confidence: 99%
“…Women with a history of a hypertensive pregnancy disorder (HPD) are ≈4 times more likely to develop hypertension later in life,4, 5 and also develop hypertension ≈10 years earlier than women who have had normotensive pregnancies 6. Hypertension in pregnancy is common, occurring in up to 10% of pregnancies worldwide,7 and may be increasing in prevalence 8.…”
Section: Introductionmentioning
confidence: 99%